ANALISA BEBERAPA SIFAT FISIKA KIMIA AIR TERHADAP ADANYA BLOOMING MICROCYSTIS AERUGINOSA KUTZ. DI BAGIAN TENGAH WADUK JATILUHUR - I NJOMAN K. KABINAWA (BERITA BIOLOGI, 1987)
I NJOMAN K.KABINAWA 1987.Analysis of some physical-chemical factors affecting the blooming of Microcystis aeruginosa Kutz. in the central part of the man made lake Jatiluhur. Berita Biologi 3(7) : 321 -325. An investigation on some physicai-chemical factors which may affect the occurence of blooming Microcystis aeruginosa Kutz.was conducted in the central part of the man made lake Jatiluhur from April to June 1981. Observation was carried out in the morning (07.30 -09.00) and in the afternoon (12.30 - 14.00) in the interval three a week. The investigation,included physical-chemical properties of the water,a quantitative and volumetric assessment of the Microcystis colonies.The water of this man made lake is considered relatively suitable for the growth of many aquatic organisms.At the commence of the blooming of the algae the oxygen, calcium, phosphate and nitrate content tend to increase, and so the water temperature.During the blooming of the Microcystis the number of colonies 39,585 and 35,685 per litre was achieved, while the volume was about 0.32 - 0.34 ml per litre.